Energy and ecology aspects of the region economy efficiency (by the example of the Chernihiv region) - Maliarenko O.Ye.; Maistrenko N.Yu. (General Energy Institute of the National Academy of Sciences of Ukraine, 2011)
The analysis of the efficiency of region's economy is given by indices of the complex estimation of energy saving measures with regard for the dynamics of the gross regional product, the consumption of fuel, and fuel intensity of the region for the period 2004-2007. Structural changes in region's economy by the types of economic activity, the structure of the consumption of fuel by types and directions, and the dynamics of emissions of harmful substances into the atmosphere from the stationary and movable sources of energy are analyzed. The suggestions aimed at a reduction of the consumption of organic fuel in the region of Ukrainian Poles'e, which suffered from the Chernobyl accident, are given.